Energy Metabolite, Immunity, Antioxidant Capacity, and Rumen Microbiota Differences Between Ewes in Late Gestation Carrying Single, Twin, and Triplet Fetuses - Jiaxin Chen; Chunhui Duan; Sicong Yue; Xiaona Liu; Jinhui Li; Yingjie Zhang; Yueqin Liu (Animals)
The objective of this study was to investigate the differences in the energy metabolites, immunity, antioxidant capacity, and rumen microbiota of ewes with different numbers of fetuses. Thirty healthy ewes were selected and divided into single- (SL, n = 10), twin- (TL, n = 10), and triplet-fetal (PL, n = 10) ewes according to the number of fetuses. Sampling was carried out on days 21 (Q21) and 7 (Q7) before lambing. The results show no differences (p > 0.05) in the DMI and BW of ewes with different numbers of fetuses, and the body condition score (BCS) of PL ewes was lower (p < 0.05) than that of SL ewes. The concentrations of β-hydroxybutyric acid (BHBA), non-esterified fatty acids (NEFA), interleukin-2 (IL-2), interleukin-6 (IL-6), and tumor necrosis factor α (TNF-α) in the PL ewes were higher (p < 0.05), while the glucose (Glu), triglyceride (TG), total cholesterol (TC), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC) values were lower (p < 0.05) than those of the SL ewes. ANOSIM analysis showed that the rumen bacterial structure of the SL, TL, and PL ewes was different on days Q21 and Q7. The relative abundance of Firmicutes and Bacteroidota in the rumen was affected (p < 0.05) by the number of fetuses: the relative abundance of Firmicutes (Ruminococcus, Butyrivibrio, Christensenellaceae_R-7_group, Lachnospiraceae_AC2044_group, Lachnospiraceae_XPB1014_group, and Anaeroplasma) was higher (p < 0.05), while that of Bacteroidota (Prevotella, Prevotellaceae_UCG-003, and Prevotellaceae_UCG-001) was lower (p < 0.05) in the SL ewes than in the PL ewes. In summary, the rumen microbial structure and energy metabolites of ewes in late gestation with different numbers of fetuses were different. Triplet-fetal ewes were characterized by lower BCS and antioxidant capacity and were prone to the triggering of inflammatory responses.